THE INFLUENCE OF BENEFITS PERCEPTION, SECURITY PERCEPTION AND EASY TO USE PERCEPTION IN USING E-WALLET - Zubaidah Hanum; Masniati Murni Ritonga; Samuel Simanjuntak (SEAN Institute, 2022)
Digital wallets are electronic applications that can be used to pay for transactions online without cards and without cash, Users only need to use their smartphone if they want to make transactions. This study used a quantitative descriptive data analysis method using a questionnaire, which is a data collection technique carried out by providing a number of statements through the G-Form to each respondent who qualifies as a research sample. The sample used in this study was 36 students of the LP3I Polytechnic Business Administration Study Program. This study aims to find out how much influence variable X has on variable Y. Based on the results of multiple linear regression analysis with a coefficient value of -5.578 and for the perception of benefits of 0.269 which means that if it is increased by 1%, the interest in use will decrease by 0.269, the Security Perception by 0.669 which means that if it is increased by 1%, the interest in use will decrease by 0.669, the perception easy to use by 0.332 which means that if it is increased by 1% then the interest in use will decrease by 0.332. Partially, this study is also significant because the sig value < 0.05 as well as the T value is calculated > T table (1,694) so it is concluded that the variables X1,X2,X3 have an effect on Y. Simultaneous tests found that F counts > F table (61,197 > 2,892) so that H0 is rejected and H1 is accepted. And the results obtained, Variable X and Variable Y have an influence of 83,3%.